Nontuberculous Mycobacteria in Patients with Cystic Fibrosis - Leung, Janice M.; Olivier, Kenneth N. (Seminars in Respiratory and Critical Care Medicine, 2013)
As a result of their underlying lung disease, patients with cystic fibrosis (CF) have a higher risk of developing nontuberculous mycobacteria (NTM) infections compared with the general population. Although NTM may be present intermittently in low amounts in the airways of CF patients without an apparent clinical effect, progressive respiratory decline due to NTM disease may also occur. Identifying this latter group of patients can be challenging for clinicians because the usual symptoms exhibited by infected individuals without CF may be difficult to distinguish from the baseline respiratory dysfunction of a patient with CF. The distinction, however, is of utmost importance because those patients with clinical worsening may benefit considerably from antimycobacterial treatment. For CF patients under evaluation for lung transplantation, NTM can play a critical role in determining overall outcomes, and treatment in the pre- and post-transplant period may be vital to success. A general approach to NTM in CF thus involves surveillance to detect NTM, careful monitoring for associated clinical decline, and consideration of treatment given for those with an otherwise unexplained deterioration. In this review, the epidemiology and clinical course of NTM in CF is described with an algorithm for management proposed.
Keywords: cystic fibrosis; nontuberculous mycobacteria; mycobacterium infections; Mycobacterium avium complex; Mycobacterium abscessus